Resenha crítica - a literatura convencional sobre crises financeiras nos países "emergentes": os modelos desenvolvidos nos anos 90 - Prates, Daniela Magalhães (Estudos Econômicos (São Paulo), 2005)
In the 90s, the succession of financial crises in the so called "emergent countries", with characteristics that haven't been considered by the first-generation models of exchange crises developed in the 80s, was followed by the emergency of new models of exchange crisis. The purpose of this article is to present these models, which have introduced in their analytical framework new elements, how the self-fulfilling expectations and the volatility of the capital flows. Firstly, we analyze the models developed after the Mexican crise, which have followed the tradition of the second-generation models that emerged after the European monetary system crise. Secondly, we examine the models developed after the Asian crise, labeled "third generation models", in which the exchange crise is intrinsically linked with a banking crise. We end up with some final considerations.